Perancangan Sistem Informasi Keuangan Siswa Pada Lembaga Kursus Pelatihan Science Society Bukittinggi - Kesumaningtyas, Febby; Pratama, Rifaldo; Aulia, Wizra; Handayani, Reti; Jihan Sy, Yulia (Pustaka Galeri Mandiri, 2025)
The design of the Student Financial Information System at the Science Society Training Course Institute in Bukttinggi functions to build an application that is expected to support the archiving of financial data which is intended to provide convenience for users to process financial data. Based on research conducted at the Science Society Training Course Institute, it can be concluded that by utilizing a computerized system, it is expected to help the decision-making process and by utilizing the Delphi 7.0 Programming Language as application software, it is expected to replace less effective and efficient methods and is expected to facilitate the creation of reports on the results of the student financial process because of the database that makes all data stored neatly and structured.